Recurrence‐free interval 12 months after local treatment of mast cell tumors in dogs using intratumoral injection of tigilanol tiglate. (22nd December 2020) - Jones, Pamela D.; Campbell, Justine E.; Brown, Graham; Johannes, Chad M.; Reddell, Paul
Abstract: Background: Tigilanol tiglate (TT) is a novel small molecule approved by the European Medicines Agency for intratumoral treatment of mast cell tumors (MCTs) in dogs. In a randomized controlled clinical efficacy and safety study in the United States, 85 of 116 dogs that received a single TT injection achieved complete response (CR) of the treated MCT by day 28. Objective: To evaluate the durability of the TT treatment response achieved at day 28 in the U.S. study by assessing MCT recurrence at the treatment site 6 and 12 months after TT administration. Animals: Eighty‐five dogs previously treated with TT. Methods: Dogs that achieved CR at day 28 were assessed retrospectively for the presence or absence of MCT at the treatment site using records from clinical visits and telephone interviews with owners. Dogs unavailable at an assessment time were considered lost‐to‐follow‐up and data for their last assessment used in the final analysis. Results: By 12 months after TT treatment, 64 dogs remained evaluable, with 21 unavailable. Of evaluable patients, 57 (89%) remained tumor free at the treatment site and 7 (11%) had developed recurrence. All recurrences occurred within the first 6 months, predominantly (5/7, 71%) within the first 12 weeks. Conclusions and Clinical Importance: Tigilanol tiglate provided a durable long‐term local response for the treatment of MCT in dogs.